2006
DOI: 10.1002/anie.200503427
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale Synthesis of H‐Antigen Oligosaccharides by Expressing Helicobacter pylori α1,2‐Fucosyltransferase in Metabolically Engineered Escherichia coli Cells

Abstract: Sugar production: A microbiological method has been developed for the production of fucosyl α1,2‐linked carbohydrates from lactose. The syntheses of 2′‐fucosyllactose and lacto‐N‐neofucopentaose‐1 (see structure), which contain the H‐2 antigen (Fucα‐2Galβ‐4R), were achieved by cultivating Escherichia coli strains that overexpressed the appropriate heterologous genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 19 publications
0
67
0
Order By: Relevance
“…[17] In contrast, other studies have not been able to reproduce this effect. [8] Thus, in this study the enzyme was generated in stand-alone form and exhibited a specific activity comparable to the reported protein fusion. [17] Although the enzyme has been demonstrated to be soluble, [13] the expression level and specific activity found in this study were much lower compared to the values published for the a1,3- [14] and a1,4-counterparts.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…[17] In contrast, other studies have not been able to reproduce this effect. [8] Thus, in this study the enzyme was generated in stand-alone form and exhibited a specific activity comparable to the reported protein fusion. [17] Although the enzyme has been demonstrated to be soluble, [13] the expression level and specific activity found in this study were much lower compared to the values published for the a1,3- [14] and a1,4-counterparts.…”
Section: Discussionmentioning
confidence: 67%
“…[21] It has been reported that disrupted futC from strain 26695 can be restored utilizing gene splicing by overlap extension for the modification of the homopolymeric tract. [8] Similarly, futC cloned from strain NCTC11639 was successfully altered in this work by a single step of site-directed mutagenesis after plasmid integration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations